Goal setting in physical education and sports sector - Sazonova, S. L.; Simonova, A. K. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to theoretically substantiate the goal setting technology application in sports and offer a goal setting application algorithm to facilitate competitive progress.